Predictions of New Horizons’ termination shock crossing - Jonathan Gasser; Justyna M. Sokół; Heather A. Elliott; Maher A. Dayeh; Kelsi N. Singer; S. Alan Stern; Igor Baliukin; Sergey Korolkov; Pontus C. Brandt; Joel W. Parker; Andrew R. Poppe; Anne J. Verbiscer; et al. (Advances in Space Research, 2026)

Habitat use differences mediate population threat exposure in white sturgeon - Jonathan A. Walter; Gabriel P. Singer; Daniel C. Reuman; Scott F. Colborne; Lawrence W. Sheppard; Daniel R. O’Donnell; Nat Coombs; Erin E. Tracy; Myfanwy Johnston; Emily A. Miller; Anna E. Steel; John T. Kelly; et al. (Environmental Biology of Fishes, 2026)

Analysis of strategies to meet ASHRAE S241 infectious aerosol control targets by space type and region using EnergyPlus™ simulations - Cary A. Faulkner; Cerrina Mouchref; Belal Abboushi; Meghan K. McNulty; Timothy I. Salsbury; Brett C. Singer; Michael D. Sohn; Gabe Arnold (Building and Environment, 2026)

Skyglow increases cyanobacteria abundance and organic matter cycling in lakes - Jeremy Fonvielle; Lukas Thuile Bistarelli; Yile Tao; Jason N. Woodhouse; Tom Shatwell; Luis A. Villalba; Stella A. Berger; Christopher C.M. Kyba; Jens C. Nejstgaard; Andreas Jechow; Franziska Kupprat; Susanne Stephan; et al. (Water Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

A Bayesian age from dispersed plagioclase and zircon dates in the Los Chocoyos ash, Central America - Alec Baudry; Brad S. Singer; Brian Jicha; Christine E. Jilly-Rehak; Jorge A. Vazquez; C. Brenhin Keller (Earth and Planetary Science Letters, 2024)

Do storm overflows influence AMR in the environment and is this relevant to human health? A UK perspective on a global issue - Holly J. Tipper; Isobel C. Stanton; Rachel A. Payne; Daniel S. Read; Andrew C. Singer (Water Research, 2024)

Comparison of effectiveness and energy use of airborne pathogen mitigation measures to meet clean air targets in a prototypical office building - Cary A. Faulkner; Timothy I. Salsbury; Belal Abboushi; Cerrina Mouchref; Brett C. Singer; Michael D. Sohn; Gabe Arnold (Building and Environment, 2024)

A river runs through it: Robust automated mapping of riparian woodlands and land surface phenology across dryland regions - Conor A. McMahon; Dar A. Roberts; John C. Stella; Anna T. Trugman; Michael B. Singer; Kelly K. Caylor (Remote Sensing of Environment, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Biodegradation, photolysis, and sorption of antibiotics in aquatic environments: A scoping review - Irene Bueno; Huan He; Amy C. Kinsley; Sarah J. Ziemann; Lauren R. Degn; André J. Nault; Amanda L. Beaudoin; Randall S. Singer; Kristine H. Wammer; William A. Arnold (Science of The Total Environment, 2023)

Mechanical ventilation and indoor air quality in recently constructed U.S. homes in marine and cold-dry climates - Chrissi A. Antonopoulos; Samuel I. Rosenberg; Haoran Zhao; Iain S. Walker; William W. Delp; Wanyu Rengie Chan; Brett C. Singer (Building and Environment, 2023)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

Analysis of Charon’s spectrum at 2.21- μ m from New Horizons/LEISA and Earth-based observations - Jason C. Cook; Silvia Protopapa; Cristina M. Dalle Ore; Dale P. Cruikshank; William M. Grundy; Carey M. Lisse; Bernard Schmitt; Anne Verbiscer; Kelsi N. Singer; John Spencer; S. Alan Stern; Harold A. Weaver (Icarus, 2023)

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Smooth muscle CaMKIIδ promotes allergen-induced airway hyperresponsiveness and inflammation - Amy M. Spinelli; Yongfeng Liu; Li-Yan Sun; José C. González-Cobos; Johannes Backs; Mohamed Trebak; Harold A. Singer (Pflügers Archiv - European Journal of Physiology, 2015)

Predictors of CNS injury as measured by proton magnetic resonance spectroscopy in the setting of chronic HIV infection and CART - J. Harezlak; R. Cohen; A. Gongvatana; M. Taylor; S. Buchthal; G. Schifitto; J. Zhong; E. S. Daar; J. R. Alger; M. Brown; E. J. Singer; T. B. Campbell; et al. (Journal of NeuroVirology, 2014)

Growth, survival, and tag retention of steelhead trout (Oncorhynchus mykiss) and its application to survival estimates - P. T. Sandstrom; A. J. Ammann; C. Michel; G. Singer; E. D. Chapman; S. Lindley; R. B. MacFarlane; A. P. Klimley (Environmental Biology of Fishes, 2013)

Airway smooth muscle STIM1 and Orai1 are upregulated in asthmatic mice and mediate PDGF-activated SOCE, CRAC currents, proliferation, and migration - Amy M. Spinelli; José C. González-Cobos; Xuexin Zhang; Rajender K. Motiani; Sarah Rowan; Wei Zhang; Joshua Garrett; Peter A. Vincent; Khalid Matrougui; Harold A. Singer; Mohamed Trebak (Pflügers Archiv - European Journal of Physiology, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Strategies for Enhancing the Effectiveness of Metagenomic-based Enzyme Discovery in Lignocellulolytic Microbial Communities - Kristen M. DeAngelis; John M. Gladden; Martin Allgaier; Patrik D’haeseleer; Julian L. Fortney; Amitha Reddy; Philip Hugenholtz; Steven W. Singer; Jean S. Vander Gheynst; Whendee L. Silver; Blake A. Simmons; Terry C. Hazen (BioEnergy Research, 2010)

New mutant versions of yeast FACT subunit Spt16 affect cell integrity - Allyson F. O’Donnell; Jennifer R. Stevens; Rosemarie Kepkay; Christine A. Barnes; Gerald C. Johnston; Richard A. Singer (Molecular Genetics and Genomics, 2009)

Acquired and Partially De Novo Synthesized Pyrrolizidine Alkaloids in Two Polyphagous Arctiids and the Alkaloid Profiles of Their Larval Food-Plants - T. Hartmann; C. Theuring; T. Beuerle; L. Ernst; M. S. Singer; E. A. Bernays (Journal of Chemical Ecology, 2004)

Shoot production in squash (Cucurbita pepo) by in vitro organogenesis - G. Ananthakrishnan; X. Xia; C. Elman; S. Singer; H. S. Paris; A. Gal-On; V. Gaba (Plant Cell Reports, 2003)

A Proposed Fog Deposition Mechanism for the Formation of Salt Efflorescences in the Mpumalanga Highveld, Republic of South Africa - A. Singer; W. F. A. Kirsten; C. Bühmann (Water, Air, & Soil Pollution, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)